Synthetic Strategies for Peroxide Ring Construction in Artemisinin - Vil’, Vera; Yaremenko, Ivan; Ilovaisky, Alexey; Terent’ev, Alexander (Molecules (Basel, Switzerland), 2017)
The present review summarizes publications on the artemisinin peroxide fragment synthesis from 1983 to 2016. The data are classified according to the structures of a precursor used in the key peroxidation step of artemisinin peroxide cycle synthesis. The first part of the review comprises the construction of artemisinin peroxide fragment in total syntheses, in which peroxide artemisinin ring resulted from reactions of unsaturated keto derivatives with singlet oxygen or ozone. In the second part, the methods of artemisinin synthesis based on transformations of dihydroartemisinic acid are highlighted.